PRODUCTION OF ELECTRICITY USING Acidithiobacillus ferrooxidans FROM THIOSULPHATE AND FERRIC IONS - Jibaja, Sandro (2019)
Acidophilic microorganisms are predominant in the ecosystems of acid mine waters, being found in abundance the species Acidithiobacillus ferrooxidans. The objective of the study was to produce electricity in the Microbial Fuel Cells (MFC) from thiosulfate at the anode and ferric ion at the cathode using the bacteria At. ferrooxidans LB151, which was characterized morphologically and molecularly. The electrochemical techniques used were chronoamperometry and cyclic voltammetry. The cyclic voltammetry show current peaks of oxidation and reduction of the compounds indicating that there is an interaction of the bacteria with the surface of the electrode. The voltage generated by the MFC is greater than the control cell, producing an average power density of 24.23 mW/m2 in 4 hours while the control cell produced an average power density of 3.41 mW/m2 in the same time. The total energy generated by the bacteria was 197.3 mW.H/m2 and the recovered Coulombs (Cp) were 4.6x10-4 C. These results indicate that using ions of thiosulfate and ferric as a substrate in the Microbial Fuel Cells and inoculating with At. ferrooxidans LB151 electricity was produced.